Pemahaman Komunikasi Mobile-AI dan Masyarakat melalui Model UTAUT2: Kasus Implementasi AI pada Platform Figma - Judhananto, Muhammad Nadhif; Natanael, Fero; Irwansyah (Philosophiamundi, 2025)
The development of artificial intelligence (AI) in mobile technology has brought significant transformations to digital work practices, particularly on collaborative design platforms such as Figma. The integration of AI in Figma not only changes the way users interact with the interface but also influences public perception and acceptance of the technology. This study aims to understand how communication between users and Mobile-AI systems is formed and socially received through a case study of Figma. The research adopts the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework to analyze the factors influencing AI adoption in mobile platforms. UTAUT2 enables a deeper examination of elements such as performance expectancy, facilitating conditions, hedonic value, and social influence within the context of emerging technology. This study employs a qualitative case study approach, involving participatory observation and in-depth interviews with Figma users in Indonesia. Data were analyzed using thematic techniques to identify patterns in communication and AI acceptance in mobile design practices. The findings indicate that performance expectancy and hedonic value are the main drivers of AI acceptance on Figma. Additionally, social influence shapes perceptions of the technology’s legitimacy and reliability. This study concludes that understanding Mobile-AI communication must take into account the social and cultural aspects of technology users, particularly in the context of AI-based collaborative design.